The role of maladaptive cognitions in gaming disorder: Differences between online and offline gaming types. (January 2021) - Bodi, Gaëlle; Maintenant, Célia; Pennequin, Valérie
Highlights: Gaming disorder concerns more online gaming type. Online players report having more maladaptive cognitions than offline players. Maladaptive cognitions equally predict both types of gaming disorder symptoms. Virtual comfort is a predictive factor of online gaming disorder symptoms only. Abstract: Gaming disorder involving online or offline games has been included in the latest International Classification of Diseases (ICD-11). Recent studies on psychological processes related to gaming disorder have identified a number of maladaptive cognitions that may play a role in developing and maintaining problematic gaming behaviors. However, there have been few studies that have examined whether these cognitions may occur differently offline versus online gaming. This study recruited 446 French-speaking adults including 229 online and 217 offline gamers (54.93 % male, Mage = 28.05), who completed a questionnaire providing information about demographic characteristics, gaming habits, cognitions related to video games, gaming disorder and psychological distress. Maladaptive cognitions correlated strongly with gaming disorder, weekly time spent on video games, depression and anxiety symptoms. Mann-Whitney U-tests revealed significant differences between online and offline gaming groups with more addicted gamers in the online group, and more maladaptive cognitions in online than offline gamers. However, regression models comparing offline and online players revealed fewer differences among predictor variables. Maladaptive cognitions predicted the two types of disorder equally, although virtual comfort appeared to be strongly predictive only of online gaming disorder. These findings are discussed in relation to addiction theory and their clinical implications.